Analysis of Early Childhood Education Policy Based on Parental Participation in Supporting Child Development - Rahmadani, Anissa Yunico; Masbirorotni, Masbirorotni; Haryanto, Eddy (FKIP - Universitas Riau, 2026)
Parental involvement in early childhood education (ECE) is a crucial factor in supporting holistic child development, yet its implementation varies across contexts and policy frameworks. This study aims to analyze ece policies that emphasize parental involvement, including its forms, influencing factors, engagement strategies, and impacts on child development. This research employs a systematic literature review (SLR) approach based on prisma guidelines, using 22 selected journal articles as data sources. Data were analyzed through thematic synthesis to identify patterns, relationships, and variations across studies. The results show that effective ece policies promote parental involvement through structured communication, school–family partnerships, parenting programs, and home-based learning support. Parental involvement is found to significantly contribute to children’s cognitive, social-emotional, and academic development. However, the level of participation is influenced by factors such as parents’ educational background, socio-economic conditions, and awareness of the importance of ece. The study also identifies that strategies based on context-sensitive and sustainable approaches are more effective in enhancing parental engagement. In conclusion, ece policies that integrate structured and sustainable parental involvement play a significant role in improving educational quality and child development outcomes. Therefore, future policies should emphasize context-based and evidence-driven approaches to strengthen parental participation.